ISOLASI DAN IDENTIFIKASI BAKTERI STAPHYLOCOCCUS EPIDERMIS PADA IKAN ASAP PINEKUHE - Ely John Karimela; Frans G Ijong; Jaka F P Palawe; Jeffri A Mandeno (Jurnal Teknologi Perikanan dan Kelautan, 2018)
Pinekuhe smoked fish is a fishery product traditionally processed by fishermen of Sangihe Island Regency. Staphylococcus epidermis is an opportunistic phatogen that causes infection to humans of weak immunity. This study aims to identify S. epidermis isolated from the Pinekuhe smoked fish. Fourty isolate samples were grown on Mannitol salt Agar medium and suspect colonies were tested for Gram staining, Catalase, Motility and Coagulase test There were 13 isolates identified as S. epidermis which characteristics as gram-positive, round shapes, clustering, 0,5Î¼m-1Î¼m in diameter, non-motilepositive catalase, and not ferment Mannitol. So, there were 32.5% S. epidermis that contaminated Pinekuhe smoked fish.